EORTC‐QLQ‐C30 and SKINDEX‐29 measurement of health‐related quality of life in patients with mycosis fungoides and Sézary syndrome: Real‐world data in Spanish patients (MICADOS Study) - Belén Navarro Matilla; Mª del Mar Onteniente Gomis; Ramon M. Pujol Vallverdú; Andrea Combalia Escudero; Irma Zapata Paz; Cristina Muniesa Montserrat; Eva González Barca; Mercedes Morillo Andújar; Amparo Pérez Ferriols; Mª Concepción Román Curto; Ricardo Fernández de Misa Cabrera; Mercedes Hospital Gil; et al. (Wiley, 2022)
Abstract Background Few studies have explored the impact of cutaneous T‐cell lymphoma (CTCL) on health‐related quality of life (HRQoL) and compared it to other patients with cancer. Objectives The primary objective of the study was to assess the QoL of patients diagnosed with the mycosis fungoides (MF) and Sézary syndrome (SS) types of CTCL in Spain. Methods A cross‐sectional observational study was completed recruiting adult patients with MF and SS, exploring the European Organisation for Research and Treatment of Cancer‐Core Quality of Life Questionnaire, version 3 (EORTC‐QLQ‐C30v3) and Skindex‐29 HRQoL and itching intensity. Results A total of 141 patients [81 males (57.4%) and mean age of 63.6 years (95% CI: 61.4-65.7)], were included. EORTC‐QLQ‐C30 global health status showed worse scores in CTCL patients compared to healthy population (p < 0.05) and did not differ from other patients with cancer. The physical and role functioning of CTCL patients were better than other patients with cancer (p < 0.05) but worse than healthy population (p < 0.05). The social functioning was similar to other patients with cancer but worse than healthy (p < 0.05). In the global health status, better scores were observed with aging (p = 0.023) and worse scores in patients with Eastern Cooperative Oncology Group (ECOG)‐1 versus ECOG‐0 (p = 0.01). The Skindex‐29 global score was 28.5 (95% CI: 24.8-32.3), being worst at higher clinical stage (p < 0.05) and at higher pruritus intensity (p < 0.001) and better for older patients (p < 0.001). More itching was related to female sex (p = 0.016), younger patients (p = 0.035), higher ECOG (p < 0.05) and higher m‐SWAT scores (p = 0.006). Conclusions These results allow mapping HRQoL affectation in CTCL patients. Global health status in MF/SS was like other patients with cancer and worse than the age‐matched healthy population. The highest impact in Skindex‐29 and EORTC‐QLQ‐C30 was associated with young age, ECOG, pruritus and disease stage.